Social entrepreneurship in Poland: problems and challenges - Agnieszka, Pacut (Journal of Public Governance, 2011)
The subject of this paper is social enterprise in Poland. It presents selected definitions of social entrepreneurship and social enterprises, and defines this problem based on Polish literature. The focus of the second part of the paper is on dilemmas concerning support for entities of social economy, including social enterprises. The author pays special attention to the use of public resources coming from structural funds, which constitute a significant source of support for these entities. In the final part of the paper, the author offers some conclusions of her analysis.